What do people include when they self-rate their health?: differential associations according to health status in community-dwelling older adults - Schüz, Benjamin Ernst Christoph; Wurm, Susanne; Schöllgen, Ina; Tesch-Römer, Clemens (Quality of life research, 2011)
Self-rated health (SRH) is widely regarded a valid and reliable indicator of health status. The validity of self-rated health has been demonstrated in many studies, for example by predicting mortality over and above medical and epidemiological data. However, the meaning of SRH can differ between individuals, especially in elderly individuals with considerable individual differences in their physical health states. It is thus important to determine whether predictors of self-rated health vary according to physical health status in order to interpret self-rated health data.